A Comparative Analysis of Itinerary Planning Algorithms for Single Mobile Agent and Multi Mobile Agent - Nidhi,; Upadhyaya, Shuchita (International Journal of Computer Sciences and Engineering, 2025)
Using Mobile Agents (MAs) every conventional distributed system work can be performed efficiently, robustly and easily within a single and general framework. Despite many benefits, Mobile Agents have a number of issues like fault tolerance, security , routing etc. Among these issues this paper emphasizes on routing of MAs. This paper defines types of itineraries based on their knowledge and based on number of Mobile Agents used to perform optimum itinerary. It describes disadvantages of single mobile agent itinerary planning(SIPs) and different challenges faced by multi mobile Agent itinerary planning(MIPs). The objective of this paper is to bring out a comparative analysis of the existing Itinerary planning algorithms.